The Hierarchical Minimax Inequalities for Set-Valued Mappings - Yen-Cherng Lin; Chin-Tzong Pang (Abstract and Applied Analysis)
We study the minimax inequalities for set-valued mappings with hierarchical process and propose two versions of minimax inequalities in topological vector spaces settings. As applications, we discuss the existent results of solutions for set equilibrium problems. Some examples are given to illustrate the established results.